Pengaruh Lokus Kendali Internal, Kemandirian, Perilaku Produktif, Pendidikan Kewirausahaan, dan Lingkungan Sosial Terhadap Intensi Berwirausaha - Siti Nur Halizah; Didit Darmawan; Rahayu Mardikaningsih (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Entrepreneurship leads to economic improvement and social advancement which is really important for the nation. This view as a force that revitalizes the economy and contributes to economic progress. Entrepreneurship in students is an interesting and relevant topic in the current situation of higher insight. Amidst the dynamic changes in the world of work, entrepreneurship has become a highly valued and needed skill. Therefore, the function of students is needed as one of the substantial to implementing entrepreneurial activities. Accordingly, the mission of this survey to recognize the effect of internal locus of control, independence, productive behavior, entrepreneurship education, and the social environment on student entrepreneurial intention. Researchers used descriptive quantitative research design and survey methods. This research is targeted at university students in Surabaya. This study involved 100 respondents and used a purposive sampling method as a data compilation technique. Research data that has been obtained from the questionnaire reactions were evaluated using multiple linear regression. The findings show that the internal locus of control has a significant influence on entrepreneurial intention. Furthermore, it shows a significant influence between independence and productive behavior on entrepreneurial intentions. This also occurs in entrepreneurship education and the social environment has a significant impact on entrepreneurial intention